Vocal-pedagogical guidelines to help methodological work with mutating voices - Lyutskanova, Doroteya (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The report examines the complex relationship between vocal science and singing, the application of scientific researches and discoveries about the physiology of sound formation as a necessary part of the methodical work of the vocal pedagogue. In recent years, the requirements for building a healthy voice, especially during a mutation, pose a number of questions to the vocal teacher: „How to interpret and apply scientific knowledge in practice? What methods should be used to achieve effective outcomes in adolescent learning? How will scientific advances in voice science enrich the methodological tools for building and preserving adolescent voices? Is science needed to interfere so deeply in the art of singing and whether the students will sing better if they are aware of the physiology and anatomy of the larynx?“ The answer to these questions can be found in the shared experience of a number of emblematic names in vocal pedagogy, which have left many vocal books, articles and teaching aids inherited.